Expression of MHC genes in adenovirus-tranformed cells - Vaessen, R.T.M.J.; Bernards, R.A.; Oostra, B.A.; Houweling, A.; Jochemsen, A.G.; Bos, J.L.; Eb, A.J. van der (Liss, 1984)
Class I MHC gene expression is drastically reduced in Ad12-, but not in Ad5-transformed primary cells of three different rodent species. Here we demonstrate that class I expression in Ad12-transformed primary Baby Rat Kidney cells can be reactivated by AdS. We also show that class I gene expression is switched off only when primary cells were transformed by Ad12, but not when established cell lines were transformed.
Keywords: Biologie